Compact LTCC balanced bandpass filter using distributed‐element resonator. Issue 5 (1st February 2013) - Chen, J.‐X.; Shao, C.; Lu, Q.‐Y.; Tang, H.; Bao, Z.‐H.
Abstract : Presented is a vertically and horizontally folded half‐wavelength resonator in a three‐dimension (3D) environment and its application to a balanced bandpass filter (BPF). Benefiting from the multilayered resonator based on the transmission line theory and low temperature co‐fired ceramic (LTCC) technology, the proposed balanced BPF can obtain compact size and good performance. For demonstration, a LTCC balanced BPF centred at 2.45GHz has been designed using the proposed resonator, and the size of the circuit is 6.0 × 5.0 × 1.6 mm 3 .